Enhancing Teachers’ Competence in Developing Lesson Plans through Continuous Guidance: A School Action Research - Muslimin, Muslimin (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Teachers are required to be able to develop lesson plans as a guide or reference for conducting learning activities. However, many teachers encounter difficulties in developing lesson plans due to various factors. Therefore, this study aims to investigate how the implementation of continuous guidance can enhance the competence of high school teachers in developing lesson implementation plans. This school action research (SAR) involved 60 teachers from MAN 2 Bone, South Sulawesi, as participants. The SAR was conducted in two cycles, with four meetings in each cycle. Data were collected through observation, questionnaires, and interviews. The findings of this SAR reveal that continuous guidance can greatly enhance teachers' ability in developing the one-page lesson plan Merdeka Belajar. The teachers' abilities in formulating learning objectives, designing learning activities, and creating assessments – the main components of the lesson plan – improved from cycle 1 to cycle 2. Furthermore, continuous guidance also improvemud the alignment of instructional implementation with the lesson plan. In the first cycle, 45% of the teachers showed good and very good performance. However, after receiving guidance, their performance in the second cycle significantly improved, with around 92% of the teachers achieving good and very good performance.Keywords: Continuous guidance, Lesson plan, School action research, Teacher competence